2016
DOI: 10.1111/jcpt.12397
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-IV inhibitors induced bullous pemphigoid: a case report and analysis of cases reported in the European pharmacovigilance database

Abstract: A search in EudraVigilance showed a disproportionality for bullous pemphigoid and gliptins, except alogliptin. These findings extend the evidence associating gliptins with this potentially serious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
1
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 6 publications
7
89
1
6
Order By: Relevance
“…[3132] Nevertheless, lymphopenia with saxagliptin (prescribing information) and higher potential of skin reaction observed with vildagliptin may theoretically suggest in favor of selective DPP-4 inhibition. [33]…”
Section: Discussionmentioning
confidence: 99%
“…[3132] Nevertheless, lymphopenia with saxagliptin (prescribing information) and higher potential of skin reaction observed with vildagliptin may theoretically suggest in favor of selective DPP-4 inhibition. [33]…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The ROR was especially high for vildagliptin relative to other DPP4-I. Some studies using pharmacovigilance databases have demonstrated a significant association between intake of DPP4-I and BP onset in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been reported that the onset of BP may be associated with the use of various drugs, such as antibiotics, antihypertensive drugs, anti-inflammatory drugs, diuretics, biopharmaceuticals, antirheumatic drugs and vaccines. [3][4][5][6][7] Most recently, an inhomogeneity analysis of BP associated with the use of DPP4-I based on the Japanese Adverse Drug Event Report database (JADER) 8 was also reported. [3][4][5][6][7] Most recently, an inhomogeneity analysis of BP associated with the use of DPP4-I based on the Japanese Adverse Drug Event Report database (JADER) 8 was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] A large-scale analysis of BP induced by DPP-4 inhibitors was performed using the European pharmacovigilance database. 7 According to the data, the proportional reporting ratio for linagliptin and BP was the second highest after that for vildagliptin. However, it has not previously been reported that the mucous membranes are severely affected in patients using DPP-4 inhibitors including linagliptin.…”
mentioning
confidence: 97%